Search for the chiral magnetic effect with charge-dependent azimuthal correlations in Xe-Xe collisions at √SNN = 5.44 TeV - Acharya, Shreyasi; Angelov, Venelin; Berdnikova, Anastasia; Bergmann, Luisa; Bórquez Cárcamo, Andrés G.; Crkovská, Jana; Danisch, Meike; Feuillard, Victor; Fokin, Ilya D.; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; et al. (Physics letters, 2024)
Charge-dependent two- and three-particle correlations measured in Xe-Xe collisions at root S-NN = 5.44 TeV are presented. Results are obtained for charged particles in the pseudorapidity range |eta| < 0.8 and transverse momentum interval 0.2 <= p(T) < 5.0 GeV/c for different collision centralities. The three-particle correlator gamma(alpha beta)=< cos(phi(alpha) +phi(beta) - 2 psi(2))>, calculated for different combinations of charge sign alpha and beta, is expected to be sensitive to the presence of the Chiral Magnetic Effect (CME). Its magnitude is similar to the one observed in Pb-Pb collisions in contrast to a smaller CME signal in Xe-Xe collisions than in Pb-Pb collisions predicted by Monte Carlo (MC) calculations including a magnetic field induced by the spectator protons. These observations point to a large nonCME contribution to the correlator. Furthermore, the charge dependence of gamma(alpha beta) can be described by a blast wave model calculation that incorporates background effects and by the Anomalous Viscous Fluid Dynamics model with values of the CME signal consistent with zero. The Xe-Xe and Pb-Pb results are combined with the expected CME signal dependence on the system size from the MC calculations including a magnetic field to obtain the fraction of CME contribution in gamma(alpha beta), f(CME). The CME fraction is compatible with zero for the 30% most central events in both systems and then becomes positive. This yields an upper limit of 2% (3%) and 25% (32%) at 95% (99.7%) confidence level for the CME signal contribution to gamma(alpha beta) in the 0-70% Xe-Xe and Pb-Pb collisions, respectively.